Mobile Sensors Deployment Subject to Location Estimation Error - Mahboubi, Hamid; Vaezi, Mojtaba; Labeau, Fabrice (IEEE transactions on vehicular technology, 2017)
Voronoi-based mobile sensor deployment algorithms require the knowledge of sensors' locations to guarantee a simple reliable coverage detection, and they miss the mark if the location is inaccurate. However, in practice, it is often too expensive to include a Global Positioning System (GPS) receiver in each node, and location information is inaccurate as sensors estimate locations from the messages they receive. We study sensor deployment algorithms in the presence of location estimation error for sensors with nonidentical sensing ranges. We propose a set of Voronoi-based diagrams, which are called guaranteed Voronoi diagrams (VDs), that guarantee single-cell-based coverage hole detection algorithms, provided that upper bounds on localization errors are assumed. Although inaccuracy of location information would appear to deteriorate the total coverage, our simulation results demonstrate that the proposed algorithms can exploit this inaccuracy to improve network coverage. Hence, even if the location information is exactly known at each node, assuming some error margins improves the network coverage if guaranteed Voronoi diagrams are used.